Promotion of experimental autoimmune encephalomyelitis upon neutrophil granulocytes' stimulation with formyl-methionyl-leucyl-phenylalanine (fMLP) peptide. (September 2015) - Kilic, Ahmet Kasim; Esendagli, Gunes; Sayat, Guliz; Talim, Beril; Karabudak, Rana; Kurne, Asli Tuncer
Abstract It has been acknowledged that neutrophil granulocytes, the common mediators of immune responses against extracellular bacteria, can also intercede autoimmune reactions such as experimental autoimmune encephalomyelitis (EAE). Formyl-methionyl-leucyl-phenylalanine (fMLP) is a microbial peptide that can be well-tolerated when intravenously administered and can directly lead to activation and accumulation of neutrophils into the blood circulation. Here, this antigenic peptide was injected to the mice at the induction of EAE, and the immunological and pathological outcomes were assessed. As a peripheral immune organ, spleen of the animals that received fMLP contained considerably high percentages of Gr-1hiLy7/4hi mature neutrophils. In the sera samples, only a slight difference was determined in Th1/Th2/Th17-related cytokine levels. Expression of CXCR1 or CXCR2 chemokine receptors was not significantly modulated in EAE with or without fMLP which might indicate a direct role for this antigenic peptide on neutrophil accumulation. Even though fMLP administration did not propone the clinical (symptomatic) onset of the disease, the animals showed severe body conditions with higher EAE scores. Accordingly, the expression of TNF-α and CXCL1 inflammatory mediators in the brain was increased in fMLP–EAE group. In conclusion, with its potent capacity to mobilize neutrophils and to stimulate innate immune cells, fMLP peptide can be used to aggravate immune reactions in EAE. This observation may indicate that the strength of innate immune responses particularly at the induction phase of EAE might influence the clinical course of the disease.